Gajalakshmi RadhakrishnanAssessment of Food Insecurity as an Indicator of Poverty among University Students Studying in Higher Educational Institutions in Tiruvallur District, Tamil Nadu, India - Gajalakshmi Radhakrishnan; SK Manivannan; Bala Ganesh Pichamuthu (Journal of Clinical and Diagnostic Research)
Introduction: Food security mainly affects college students, even though countrywide schemes like the Public Distribution System (PDS) and mid-day meal programmes exist in India. However, students studying in postgraduate educational institutions, especially those from low-income or rural families, are more likely to experience food insecurity, emphasising the significance of targeted interventions and support systems on campus. Aim: To assess the prevalence and determinants of food insecurity among university students in Higher Educational Institutions (HEIs) in Tiruvallur District, Tamil Nadu, India. Materials and Methods: This was a cross-sectional study conducted in five HEIs located in rural areas of Tiruvallur District, Tamil Nadu, India, between January and March 2024. A total of 940 students participated, selected using a stratified random sampling technique. Data were collected using a bilingual (English and Tamil) version of the Household Food Insecurity Access Scale (HFIAS), which had been pretested and found to be reliable (Cronbach’s alpha = 0.916). Parameters evaluated included age, gender, marital status, education level, parental occupation, family income, type of accommodation, financial issues at home, and food insecurity score. Data were analysed using STATA software. Descriptive statistics, chi-square tests, and binary logistic regression were applied to identify determinants of food insecurity. Results: The prevalence of food insecurity among the students was 34.1%. Female students or those who had financial stresses at home had higher odds of food insecurity. Living in college-hostel accommodation had significantly lower odds of food insecurity (OR=0.271, p<0.001). Conclusion: A significant number of university students experienced food insecurity, which was considerably linked to female gender, financial hardship, and living arrangements. Interventions, including subsidised meal programmes, campus food banks, and financial literacy education, should be considered moving forward to address this widespread and overlooked public health issue.